A retrospective study on risk assessment and management of forensic psychiatric inpatients in Hong Kong. (16th July 2020) - Siu, Bonnie W.M.; So, Jane W.L.; Yuen, K.K.; Chan, Anita W.L.; Chan, Clement; Lai, Eric S.K.; Leung, H.W.; Lam, M.
Abstract: The Department of Forensic Psychiatry of Castle Peak Hospital is the only facility in Hong Kong that provides territory‐wide forensic psychiatric services for patients with criminal involvement. This retrospective study aimed to explore whether the rehabilitation programs provided by the department could significantly reduce the risks of forensic psychiatric inpatients as measured by the Short‐Term Assessment of Risk and Treatability (START). START ratings of inpatients who were hospitalized in the department for more than 3 months and were discharged to the community during the period from 11 April 2015 to 31 March 2019 were analyzed. A total of 79 patients were assessed, of whom 61 (77.2%) were males. Fifty‐four (68.4%) patients suffered from schizophrenia. START scores upon admission (strength score = 5.67; vulnerability score = 17.43) and upon discharge (strength score = 6.87, vulnerability score = 11.18) indicated significant reduction of risks among inpatients ( p < 0.05).